Neurodegeneration and Early Infantile Epilepsy Associated with ITPA Variants: A Case Series and Review of Literature - Sharma, Yashu; Saini, Arushi Gahlot; Kaur, Rajdeep; Bhatia, Vikas; Didwal, Gunjan; Kumar, Pawan; Uppala, Revathi (Neuropediatrics, 2022)
Background Inosine triphosphate pyrophosphohydrolase (ITPase) deficiency associated with mutations in the ITPA gene is a recently characterized purine pathway defect that presents with early infantile epileptic encephalopathy and lethal course. This disorder is rare, and only 12 cases are reported worldwide.Methods We report two additional cases of ITPA-associated neurodegeneration and two pathogenic compound heterozygous variants. We also reviewed the previously published cases of ITPA-associated encephalopathy.Results Both cases presented with progressive infantile-onset encephalopathy, severe developmental delay, microcephaly, facial dysmorphism, and epilepsy. Together with the presented two cases, 14 cases were available for analysis. The mean age of presentation was 16.7 ± 12.4 months (range 3–48 m). The most common clinical features at presentation were developmental delay, seizures, microcephaly, and hypotonia, seen in all 14 (100%) patients. The mean age of seizure onset was 4.75 months (range 2–14 m). Cardiomyopathy was noted in 42% of patients where it was explicitly evaluated (n = 5/12). Consanguinity was reported in 77% of the cases. The cardinal neuroradiological features are T2-signal abnormalities and diffusion restriction in the long tracts, especially the posterior limb of the internal capsule and the optic radiation. The majority of the patients died before 4 years of age (85.7%).Conclusion ITPA-related encephalopathy presents with infantile-onset neurodegeneration, progressive microcephaly, and epilepsy. Progressive brain atrophy and diffusion restriction in the white matter tracts are important radiological clues.
Keywords: purine; inborn errors of purine metabolism; ITPA gene; infantile encephalopathy; brain atrophy